Using self-drilling screws in volar plate osteosynthesis for distal radius fractures: a feasibility study. Issue 1 (December 2016) - Synek, Alexaner; Borgmann, Lars; Traxler, Hannes; Huf, Wolfgang; Euler, Ekkehard; Chevalier, Yan; Baumbach, Sebastian
Abstract Background Symptomatic extensor tendon irritation is a frequent complication in volar plate osteosynthesis of distal radius fractures. It is typically caused by dorsal screw protrusion and overdrilling of the dorsal cortex. The use of self-drilling locking screws (SDLS) could overcome both causes. The practical applicability of SDLS depends on two prerequisites: (1) the feasibility of preoperative distal screw length determination, and (2) sufficient primary biomechanical stability of SDLS compared to standard locking screws (SLS). Methods We first assessed the feasibility of preoperative screw length determination (1): Distal radius width, depth and distal screw lengths were measured in 38 human radii. Correlations between distal radius width and depth were assessed, a cluster analysis (Ward's method and squared Euclidean distance) for distal radius width conducted, and intra-cluster screw lengths analyzed (ANOVA). The biomechanical performance of SDLS (2) was assessed by comparison to SLS in a distal radius fracture model (AO-23 A3). 75 % distal screw length was chosen for both groups to simulate a worst-case scenario. Uniaxial compression tests were conducted to measure stiffness, elastic limit, maximum force and residual tilt. Statistics comprised of independent sample t-tests and a Bonferroni correction (p  < 0.0125). Results (1) Distal radius width and depth showed a high correlation (R 2  = 0.79;p  < 0.001). Three distal radius width clusters could be identified: small <34 mm; medium 34–36.9 mm; large >36.9 mm. ANOVA and Tukey post-hoc analysis revealed significantly different volar-dorsal depths (p  < 0.05) for nearly all screws. (2) To assess biomechanical stability nine specimens were tested each; no significant differences were found between the SDLS and SLS groups. Conclusions This feasibility study demonstrates that (1) distal radius width can be used as a predictor for distal screw length and (2) that SDLS provides mechanical stability equivalent to SLS. These results highlight the feasibility of applying SDLS screws in volar plate osteosynthesis at least in extraarticular fractures.